A106 BENZOCAINE-INDUCED METHEMOGLOBINEMIA: A RARE BUT POTENTIALLY FATAL COMPLICATION OF TOPICAL ANESTHETIC USE IN ESOPHAGOGASTRODUODENOSCOPY. (4th March 2021) - Ricci, M; Gillis, C
Abstract: Background: Methemoglobinemia is an uncommon and potentially lethal condition arising when the iron moiety of heme is oxidized from the ferrous (Fe 2+ ) to ferric (Fe 3+ ) state, causing a disruption of O2 binding and impairment of O2 delivery to tissue. There are two forms of methemoglobinemia: inherited and acquired. Acquired methemoglobinemia is caused by medications, including topical anesthetics (TAs) used in esophagogastroduodenoscopy (EGD). Aims: To raise awareness of this serious complication of TA use. Methods: A 66-year old woman underwent EGD for dysphagia and globus sensation. Her past medical history included gastroesophageal reflux disease, paraoesophageal hernia, coronary artery disease, and hypertension. Prior to EGD, her oropharynx was anesthetized with benzocaine spray and she was sedated with fentanyl 100 mcg and midazolam 3 mg. EGD was unremarkable. At completion she required no supplemental oxygen (SpO2 96%). In recovery, she became drowsy and cyanotic. Vital signs revealed an SpO2 of 86% that did not improve with 4L supplementary O2 via nasal prongs. Aside from cyanosis, physical examination was normal. ECG, chest X-ray, and CT scan with pulmonary embolism protocol did not identify a cause for hypoxia. Arterial blood gas (ABG) revealed dark brown blood with an Pa O2 of 397 mmHg. Methemoglobinemia was suspected and confirmed with a serum methemoglobin (MHg) level of 18% (ref <3%). Results: Intravenous methylene blue (1g/kg) was administered with complete resolution of symptoms. She was admitted for monitoring and discharged the next day with no sequelae. Conclusions: Methemoglobinemia is a rare condition (incidence 1/7000 procedures) of increased MHg due to the oxidation of iron in heme, compromising oxygen binding/offloading and delivery to tissues. Normal MHg levels are <3%, which is maintained by NADH-MHg reductase. This enzyme reduces Fe 3+ to Fe 2+ . TAs cause elevated methemoglobinemia by oxidizing iron (Fe 2+ to Fe 3+ ) at a rate 100-1000x faster than NADH-MHg reductase can reduce it. Benzocaine has been associated with a 3.7- fold higher risk of methemoglobinemia than other topical anesthetics, and the risk is not dose-dependent. Presentation varies with degree of MHg. Hallmark signs of cyanosis, impaired SpO2 with normal ABG, and "chocolate-colored" blood occur at levels>10%. Death/coma occurs at levels >50%. Incidence is idiosyncratic; however, those with smoking history or underlying cardiac/lung disease are at elevated risk for poor outcomes. The activity of NADH-MHg reductase is increased by methylene blue. When administered at doses of 1-2g/kg, it rapidly reduces MHg, restoring the physiological equilibrium. TAs are used routinely in EGD. Gastroenterologists who use TAs in procedures need to be aware of the association between TAs and methemoglobinemia. Prompt recognition/treatment will prevent morbidity/mortality. Funding Agencies: None